Combined Housing and Transportation Affordability in Peri-Urban Region - Rahmah, Ihdiny Mauhiya Miftahar; Swasto, Deva Fosterharoldas (CAKRAWALA, 2020)
The peripheral area is considered as a preferable location for having affordable housing. However, the transport costs that appear as a consequence of the housing location might take up a considerable share of the household’s income. This study aimed to identify the combined housing and transportation (CHT) affordability in the peri-urban region of the Surabaya Metropolitan Area. A survey was conducted in three subdistricts of the Sidoarjo Regency, which are Waru, Gedangan and Sidoarjo sub-districts. The result showed that those three areas are affordable if only the housing costs are considered. However, they are unaffordable if transports costs are included. This suggests that the CHT affordability might depict the true affordability if the transportation costs are included. Therefore, this study suggests that a comprehensive land use planning might be needed in order to create sustainable development.